Genome Plasticity in Cultured Leishmania donovani: Comparison of Early and Late Passages - Sinha, Roma; C, Mathu Malar; Raghwan,; Das, Subhadeep; Das, Sonali; Shadab, Mohammad; Chowdhury, Rukhsana; Tripathy, Sucheta; Ali, Nahid (Frontiers in Microbiology, 2018)
Abstract Leishmania donovani possesses a complex heteroxenic life cycle where infective metacyclic promastigotes are pre-adapted to infect their host and cope up with intracellular stress. Exploiting the similarities between cultured and sandfly derived promastigotes, we used early and late passage cultured promastigotes to show specific changes at genome level which compromise pathogen fitness reflected in gene expression and infection studies. The pathogen loses virulence mostly via transcriptional and translational regulations and long-time cultivation makes them struggle to convert to virulent metacyclics. At the genomic level very subtle plasticity was observed between the early and the late passages mostly in defense-related, nutrient acquisition and signal transduction genes. Chromosome Copy number variation is seen in the early and late passages involving several genes that may be playing a role in pathogenicity. Our study highlights the importance of ABC transporters and calpain like cysteine proteases in parasite virulence in cultured promastigotes. Interestingly, these proteins are emerging as important patho-adaptive factors in clinical isolates of Leishmania. We found that the currently available genome of Leishmania in the NCBI database are from late passages. Our early passage genome can act as a reference for future studies on virulent isolates of Leishmania. The annotated leads from this study can be used for virulence surveillance and therapeutic studies in the Indian subcontinent.